1991
DOI: 10.1128/jvi.65.7.3949-3953.1991
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic stability of foot-and-mouth disease virus variants on serial passage in cell culture

Abstract: Two neutralizing monoclonal antibody (MAb)-resistant variants selected from an isolate of foot-and-mouth disease virus (FMDV) type A5 were repeatedly passaged in cell culture and monitored for susceptibility to neutralization by the selecting MAb. A variant isolated with a MAb to a conformational epitope (1-OG2) lost resistance in 20 passages, while a variant isolated with a MAb to a linear epitope (1-HA6) persisted for 30 passages. In both cases, the virus population emerging after passage was antigenicaily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The absence of changes in the G gene also does not eliminate the possibility of changes in other parts of the viral genome. Our results are consistent with previous studies that passage of the virus through a few generations of cell culture does not typically result in virus evolution (Gonzalez et al 1991, Chen et al 2003, Bellec et al 2014. Additional studies examining whether or not multiple rounds of serial passage through fish results in evolution may be enlightening.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of changes in the G gene also does not eliminate the possibility of changes in other parts of the viral genome. Our results are consistent with previous studies that passage of the virus through a few generations of cell culture does not typically result in virus evolution (Gonzalez et al 1991, Chen et al 2003, Bellec et al 2014. Additional studies examining whether or not multiple rounds of serial passage through fish results in evolution may be enlightening.…”
Section: Discussionsupporting
confidence: 92%
“…Foot-and-mouth disease virus (FMDV) is an aphthovirus of the family Picornaviridae which causes an economically important disease of cattle and other cloven-hoofed animals (reviews in references 2, 6, 20, and 57). FMDV populations are genetically and antigenically heterogeneous (9, 12-17, 27, 47, 51, 58, 60, 63), and variants showing different competitive abilities relative to their parental populations arise at high rates (28,46). Thus, the virus conforms to a quasispecies structure, a feature shared with most other RNA viruses and retroviruses (7, 11, 18, 19, 31-36, 40, 43, 53, 59, 67, 68).…”
mentioning
confidence: 99%
“…Cell culture adaptation of virus leading to increase in sensitivity to in vitro neutralization has been reported in a number of viruses including HIV‐1, SIV, and FMDV [Gonzalez et al, ; Sullivan et al, ; Means et al, ]. Marsh et al [] reported a similar phenomenon for hRSV.…”
Section: Discussionmentioning
confidence: 89%